Re-imagining cultural studies : the promise of cultural materialism - Milner, Andrew (Sage, 2002)
Re-imagining Cultural Studies restores Williams to a central position in relation to the formation and development of cultural studies. The book is a much-needed reappraisal of the Williams approach, correcting misinterpretations and demonstrating its singular relevance to the problems and potentials facing cultural studies today.